Effect of microgravity on glial cell line‐derived neurotrophic factor and cerebral dopamine neurotrophic factor gene expression in the mouse brain. Issue 9 (6th May 2015) - Tsybko, A.S.; Ilchibaeva, T.V.; Kulikov, A.V.; Kulikova, E.A.; Krasnov, I.B.; Sychev, V.N.; Shenkman, B.S.; Popova, N.K.; Naumenko, V.S.
Abstract : Mice were exposed to 1 month of space flight on the Russian biosatellite BION‐M1 to determine its effect on the expression of genes involved in the maintenance of the mouse brain dopamine system. The current article focuses on the genes encoding glial cell line‐derived neurotrophic factor (GDNF) and cerebral dopamine neurotrophic factor (CDNF). Space flight reduced expression of the GDNF gene in the striatum and hypothalamus but increased it in the frontal cortex and raphe nuclei area. At the same time, actual space flight reduced expression of the gene encoding CDNF in the substantia nigra but increased it in the raphe nuclei area. To separate the effects of space flight from environmental stress contribution, we analyzed expression of the investigated genes in mice housed for 1 month on Earth in the same shuttle cabins that were used for space flight and in mice of the vivarium control group. Shuttle cabin housing failed to alter the expression of the GDNF and CDNF genes in the brain structures investigated. Thus, actual long‐term space flight produced dysregulation in genetic control of GDNF and CDNF genes. These changes may be related to downregulation of the dopamine system after space flight, which we have shown earlier. © 2015 Wiley Periodicals, Inc. Significance: Our results provide the first evidence of microgravity effects on expression of the GDNF and CDNF neurotrophic factor genes. A considerable decrease in mRNA level of GDNF and CDNF in the nigrostriatal dopamine system was found. Because both GDNF and CDNF play a significant role in maintenance and survival of brain dopaminergic neurons, we can assume that this dysregulation in genetic control of GDNF and CDNF genes in substantia nigra could be among the reasons for the deleterious effects of space flight on the dopamine system. Abstract : A: Space flight reduced expression of the GDNF gene in the striatum and hypothalamus but increased it in the frontal cortex and raphe nuclei area. B: Expression of the investigated genes in mice housed for 1 month on Earth in the same shuttle cabins that were used for space flight and in mice of the vivarium control group. C: Actual space flight reduced expression of the gene encoding CDNF in the substantia nigra but increased it in the raphe nuclei area. D: Shuttle cabin housing failed to alter the expression of the GDNF and CDNF genes in the brain structures investigated.